Avena sativa (Oat), A Potential Neutraceutical and Therapeutic Agent: An Overview - Singh, Rajinder; De, Subrata; Belkheir, Asma (Critical reviews in food science and nutrition, 2013)
The aim of the present review article is to summarize the available information related to the availability, production, chemical composition, pharmacological activity, and traditional uses of Avena sativa to highlight its potential to contribute to human health. Oats are now cultivated worldwide and form an important dietary staple for the people in number of countries. Several varieties of oats are available. It is a rich source of protein, contains a number of important minerals, lipids, β-glucan, a mixed-linkage polysaccharide, which forms an important part of oat dietary fiber, and also contains various other phytoconstituents like avenanthramides, an indole alkaloid-gramine, flavonoids, flavonolignans, triterpenoid saponins, sterols, and tocols. Traditionally oats have been in use since long and are considered as stimulant, antispasmodic, antitumor, diuretic, and neurotonic. Oat possesses different pharmacological activities like antioxidant, anti-inflammatory, wound healing, immunomodulatory, antidiabetic, anticholesterolaemic, etc. A wide spectrum of biological activities indicates that oat is a potential therapeutic agent.